Antenatal Ultrasound Findings in Fetus with Down Syndrome - Mehmet Serdar KÜTÜK; Mahmut Tuncay ÖZGÜN; Mehmet Dolanbay; Gülsüm Uysal; Aslı Uzak; Elif Kulengir; Semih Uludağ; Mustafa Başbuğ (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of the present study is to assess the importance and role of the ultrasound imaging in the diagnosis of Down syndrome based on our own experience. STUDY DESIGN: The study was conducted in Erciyes University, Department of Obstetrics and Gynecology, Prenatal Diagnosis Unit between 2010-2012. The data of 67 fetus prenatally diagnosed as Down syndrome were analyzed retrospectively with special emphasizes on ultrasound findings. RESULTS: A total of 67 women were included in the study. The main maternal age 33.5 (min-max: 18-46). The most common indication for invasive testing was advanced maternal age (23.8%). The invasive testing consisted of chorionic villus sampling (10.4%), amniocentesis (83.5%), and cordocentesis (5.9%). In 54 patients, the ultrasonographic evaluation revealed major malformation and/or Down syndrome marker (80.5%), and 38 cases had more than one marker/malformation (56.7%). The most common Down syndrome marker was mild pyelectasia (25.3%), and the most common major congenital anomaly was atrioventricular canal defect that was seen in six fetuses (8.9%). CONCLUSION: Despite improvement in ultrasound technology and experiences, no anomaly and/or aneuploidy marker can be detected with ultrasound in a considerable proportion of fetus with Down syndrome. Therefore, invasive prenatal testing should be standard of care in the presence of abnormal serum screening for Down syndrome and/or in pregnant women of advanced maternal age.